2019
DOI: 10.1111/sed.12657
|View full text |Cite|
|
Sign up to set email alerts
|

Threshold of motion of bivalve and gastropod shells under oscillatory flow in flume experiments

Abstract: The threshold of motion of non‐fragmented mollusc shells was studied for the first time under oscillatory flow. In this regard, flume experiments were used to investigate the threshold of motion of three bivalve and three gastropod species, two typical mollusc classes of coastal coquina deposits. The sieve diameters ranged from 2·0 to 15·9 mm. These experiments were performed on a flat‐bottom setup under regular non‐breaking waves (swell) produced by a flap‐type wave generator. The critical Shields values for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…() and Fick et al . () found that thresholds of motion of bioclastic particles are within or below the threshold envelope for siliciclastic sediment when considering particle sieve diameters. Because bioclastic particles have significantly lower settling velocities than siliciclastic sediments with similar entrainment thresholds, once such a platy shell fragment is initiated, it can be transported further than the sand particle with comparable critical bed shear stress.…”
Section: Discussionmentioning
confidence: 99%
“…() and Fick et al . () found that thresholds of motion of bioclastic particles are within or below the threshold envelope for siliciclastic sediment when considering particle sieve diameters. Because bioclastic particles have significantly lower settling velocities than siliciclastic sediments with similar entrainment thresholds, once such a platy shell fragment is initiated, it can be transported further than the sand particle with comparable critical bed shear stress.…”
Section: Discussionmentioning
confidence: 99%
“…The threshold of deposition of marine biota varies significantly between species, since bioclastic particles derived from them have varied densities and shapes (Rieux et al ., 2019). Previous flume tank experiments found the shear stresses at threshold of motion for both broken and non‐fragmented bioclastic particles were an order of magnitude lower or similar to siliciclastic particles of the same sieve diameter, due to their irregular shapes (Komar & Li, 1986; Flemming, 2017; Joshi et al ., 2017; Fick et al ., 2020). Threshold stresses are also typically larger by up to a factor of three for more poorly sorted sediments (McCarron et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several types of density circulate in the literature (Fig. 5), some with contrasting definitions, including bulk density (Oehmig, 1993), dry bulk specific density (Weber et al, 1969), bulk skeletal density (Sadd, 1984), skeletal density (Morgan and Kench, 2014), solid density (Allen, 1984), mineral density (Milan et al, 1999), material density (Smith and Cheung, 2003), sediment density (Prager et al, 1996;Paphitis et al, 2002;Joshi et al, 2014;Fick et al, 2020), sediment grain density (LaBarbera, 1981), grain density (Kench and McLean, 1997), particle density (Kench and McLean, 1997;Cuttler et al, 2017), object density (Caromel et al, 2014), average sediment density, (Neumann and Land, 1975) sphere-equivalent density (Michels, 2000), average density (Diedericks et al, 2018;Li et al, 2020), apparent density (Jorry et al, 2006), relative density (Dey, 2003) effective density (Wanless et al, 1981;Fok-Pun and Komar, 1983;Kench and McLean, 1996) and specific gravity determination (Jell et al, 1965) (Table S1 in Supplementary Data). Some of these definitions are the same, others use the same term but wield different definitions.…”
Section: Sediment Densitymentioning
confidence: 99%
“…Several studies have investigated the link between settling velocity and entrainment properties of carbonate grains. For example, taphonomic features, such as symmetry and concavo-convexity, control the settling mode and entrainment thresholds of single bivalve shells (Allen, 1984;Olivera and Wood, 1997;Rieux et al, 2019;Li et al, 2020;Fick et al, 2020). Weill et al (2010) emphasised the dual nature of shell fragments, which exhibit low settling velocities in combination with a high resistance to flow friction once deposited (bed roughness).…”
Section: Transport Of Bioclastic Carbonate Grainsmentioning
confidence: 99%
See 1 more Smart Citation